Gambaran Pelaksanaan 5 Pilar Sanitasi Total Berbasis Masyarakat di Kelurahan Kasturian Kota Ternate: Description Of The Implementation Of The 5 Pillars Of Community-Based Total Sanitation In Kasturian Village, Ternate City - Vebby Regista; Aida Fitria; Masni A Kadir (Svasta Harena: Jurnal Ilmiah Gizi, 2021)
Environmental health is important in improving public health, one of the environmental health problems is poor sanitation. Sanitation improvement is included in the improvement target in Indonesia to achieve the 2030 Suntainable Development Goals (SDG's), currently it is still an obstacle due to lack of public awareness of environmental sanitation such as household problems with open defecation, household waste treatment, clean water and garbage treatment. The incidence of diarrhea in the Work Area of the Siko Health Center, 11.8% (24 cases) of 202 cases of diarrhea in 2020 Occurred in Kasturian Village, Ternate City. The purpose of the study was to determine the description of the implementation of the 5 Pillars of Community-Based Total Sanitation (Stbm) in Kasturian Village, Ternate City in 2021. Descriptive research method with quantitative analysis techniques on 43 respondents in Kasturian Village, Ternate City. Data obtained by using a questionnaire using Google Form and analyzed using SPSS Software. The results of the analysis show that Pillar 1 of Stop Opening Open Defecation (BABS), it is known that there is still Inappropriate Sanitation / Cubluk 20.9% . Pillar 2 Community-Based Total Sanitation Washing Hands with Soap (CTPS) is known to be true for CTPS 83.7. Pillar 3 stores food equipment correctly 90.7%, stores food processing equipment correctly 95.3%, closes food and beverages correctly: 100%. Pillar 4 Household Waste Management There is no waste scattered around the house 62.8%, and Pillar 5 only 27.9% in waste water management connected to the Communal Wastewater Treatment Plant (IPAL)Keywords: Stbm, Sanitation, Kesling, Ternate